(untitled) (Scottish Historical and Archaeological Internet Reports, 2005)
In general, the archaeobotanical assemblage represents a mix of material relating to the fuel source and other plant material incorporated into the fire. Many of the carbonized plant macrofossils relate to the burning of peaty turf. They include relatively large quantities of small culm bases, nodes and rhizome fragments, fibrous burnt peat and seeds and other plant components of heathers, sedges, and grasses, notably heath-grass.